ICT based market information services in Kerala – determinants and barriers of adoption - M. Anoop; N. Ajjan and K.R. Ashok (Economic Affairs, 2015)
ICT based market information services are getting wide importance as a means of empowering farmers by enabling them to take informed decisions, and in removing information asymmetry. This study analyses determinants of adoption as well as barriers to adoption of ICT based market information services (MIS) in Kerala. Logistic regression model revealed that factors like education, family size, and contact with extension agent positively influenced adoption of ICT based market information services by the farmers whereas income from other sources negatively influenced the adoption. Technical barriers and language were found to be the most important barriers for adoption of MIS followed by irrelevancy of contents, lack of reliability, lack of awareness and cost involved. The study suggested that further efforts to create awareness about such interventions among farmers, providing content in local languages in user friendly manner will increase the adoption of MIS and would remove information asymmetry in agricultural marketing